An introduction to real analysis - Bhat, V.K (Alpha Science International, 2012)
"An Introduction to Real Analysis" covers some basic results pertaining to the set of real numbers. It is a foundational course for beginners. It includes chapters like real number system, sequences, limit and continuity of functions, differentiability and integration. A chapter on inequalities supplements other chapters. Each chapter contains some examples and an exercise set. Solving these exercises will make the subject interesting. Pre requistte for this book is the basic knowledge of real numbers.